Geochemical behaviours of chemical elements during subduction-zone metamorphism and geodynamic significance. Issue 10 (26th July 2016) - Xiao, Yuanyuan; Niu, Yaoling; Wang, Kuo-Lung; Lee, Der-Chuen; Iizuka, Yoshiyuki
ABSTRACT: Seafloor subduction and subduction-zone metamorphism (SZM) are understood to be the very cause of both subduction-zone magmatism and mantle compositional heterogeneity. In this article, we compile geochemical data for blueschist and eclogite facies rocks from global palaeo-subduction-zones in the literature, including those from the Chinese Western Tianshan ultrahigh pressure (UHP) metamorphic belt. We synthesize our up-to-date understanding on how chemical elements behave and their controls during subduction-zone metamorphism. Although the compositional heterogeneity of metamorphic minerals from subducted rocks has been recently reported, we emphasize that the mineral compositional heterogeneity is controlled by elemental availability during mineral growth, which is affected by the protolith composition, the inherited composition of precursor minerals, and the competition with neighbouring growing minerals. In addition, given the likely effects of varying protolith compositions and metamorphic conditions on elemental behaviours, we classify meta-mafic rocks from global palaeo-subduction-zones with varying metamorphic conditions into groups in terms of their protolith compositions (i.e. ocean island basalt (OIB)-like, enriched mid-ocean ridge basalt (MORB)-like, normal [N]-MORB-like), and discuss geochemical behaviours of chemical elements within these co-genetic groups rather than simply accepting the conclusions in the literature. We also discuss the geochemical consequences of SZM with implications for chemical geodynamics, and propose with emphasis that: (1) the traditionally accepted 'fluid flux induced-melting' model for arc magmatism requires revision; and (2) the residual subducted ocean crust cannot be the major source material for OIB, although it can contribute to the deep mantle compositional heterogeneity. We also highlight some important questions and problems that need further investigations, e.g. complex subduction-zone geochemical processes, different contributions of seafloor subduction and resultant subduction of continental materials, and the representativeness of studied HP–UHP metamorphic rocks.